Nutritional quality, oxidation, and sensory parameters in fillets of common carp (Cyprinus carpio L.) influenced by frozen storage (–20 °C). Issue 5 (2nd February 2018) - Hematyar, Nima; Masilko, Jan; Mraz, Jan; Sampels, Sabine
Abstract: The aim of this study was to find the effects of frozen storage on lipid and protein oxidation, firmness, liquid loss, sensory properties, and nutritional values in common carp ( Cyprinus carpio ) fillets during 6 months of frozen storage (–20 °C). Thiobarbituric acid‐reactive substances, peroxide value, and carbonyl concentration were significantly increased after the 4th, 2nd, and 8th weeks, respectively. The firmness of fillets decreased, whereas the liquid loss increased. In contrast, sensory evaluation did not show any significant changes. The amount of monoacylglycerols and diacylglycerols decreased significantly after 8 weeks. The L * and b * values increased significantly after the 16th and 3rd weeks but a * showed a minor increase. The value of pH increased significantly until the 4th week. The results indicate that the development of lipid and protein oxidation was not intense in the period of 24 weeks of frozen storage, and the fish was in an acceptable condition. Practical applications: The demand of consumers for carp is increasing owing to the high content of essential polyunsaturated fatty acids. However, deterioration of fish fillets during the storage time can be a major problem as it leads to a loss of market acceptability. Therefore, monitoring the changes in lipids, proteins, sensory aspects, nutritional quality, and firmness during frozen storage is important. This study showed that after 24 weeks of storage at −20 °C, the products of lipid and protein oxidation increased but all the measured quality parameters were still within acceptable values.